Knowledge and Thinking Skills in Li-Pro-GP Model of Instruction - Pantiwati, Yuni; Kusniarti, Tuti; Permana, Fendy Hardian; Nurrohman, Endrik; Amin, Astuti Muh.; Sari, Tasya Novian Indah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Surveys from some research on Indonesian student’s literacy skills showed irregularity with Indonesia's literacy rate. Therefore, it can be said that most of Indonesians have already been literate, in terms of education. Nonetheless, their literacy skills in common still remains weak. Moreover, student’s low literacy skills are deemed as the result of low interest at reading. A number of problems in reading skill is closely associated with limited reading experiences and practices. The current research aims to describe student’s knowledge and thinking skills in a Li-Pro-GP model of instruction. The syntax of this learning model is project-based learning that is integrated with the School Literacy Movement (SLM) and Character Education Reinforcement (CER) programs. The research fell into a descriptive research model. Research subjects, seventh graders attending IPA instructions. Data of the research were analyzed descriptively, which indicated improvement in terms of knowledge and thinking skills amidst students. In addition, the highest level of language use was found at the test for Aspect C2, C4, C5, and C6, whilst the highest level of conceptual truth was indicated at Aspect C3. On the other hand, the lowest level of giving argumentation appeared at all aspects. In sum, the highest level of skills was indicated by the language use, while the lowest at the student’s confidence in giving argumentation.